Descriptive Study On The Use Of Traditional Medicine By Patients With Chronic Diseases - Kasmara, Dwi Pratiwi; Tawil, Muh. Risal; Ganoko, Marwan Ahmad; Putri, Safridha Kemala; Mainassy, Meillisa Carlen; Rahmat, Rezqiqah Aulia (Sean Institute, 2024)
This study investigates the use of traditional medicine by patients with chronic diseases to understand the factors that influence this practice. The aim of the study was to identify patterns of traditional medicine use, perceived effectiveness, and factors that influence usage decisions. The method used was in-depth interviews with 10 participants representing a variety of ages, genders, and socio-economic backgrounds. The results showed that cultural beliefs, social environmental influences, and perceived effectiveness of traditional medicine play an important role in usage decisions. The implication of this study is the need for an integrated approach in chronic disease management, which incorporates the appropriate use of traditional medicine with conventional medical practices to improve the quality of treatment.